ASSESSMENT OF THE DIFFERENT SIZE LEAD SULPHIDE NANOPARTICLES INFLUENCE ON ERYTHROCITES AND BLOOD PLASMA IN VITRO - Gubar, I.V.; Sokurenko, L.M.; Kaminsky, R.F.; Oliinyk, T.M.; Chaikovsky, Yu.B.; Yavorovsky, O.P. (World of Medicine and Biology, 2020)
Disclosure of mechanisms for the implementation of toxic effects of lead compounds becomes necessary to assess the potential risks of their industrial use and to develop effective prevention measures. The aim of the study was evaluation in vitro of biochemical changes in rats erythrocytes and blood plasma under the action of lead sulfide nanoparticles depending on their size and their concentration. The obtained results showed a statistically significant increase in the antioxidant enzymes and the level of thiol groups activity in erythrocytes and blood plasma, as well as changes in the concentration of TBA(thiobarbituric acid)-active products and diene conjugates in erythrocytes under the action of lead nanoparticles. Biochemical changes in plasma and erythrocytes had the same tendencies, with erythrocytes parameters undergoing greater changes. The effect of PbS26-34 showed a more active toxic effect, especially in dilutions of 10-3-10-4 Mol/l.
Keywords: lead; nanoparticles; erythrocytes; blood; antioxidant system; lipid peroxidation products; oxidative stress